Experimental study on the effect of non-condensable gas dissolved in sub-cooled water on steam jet condensation in a rectangular channel. (May 2019) - Fu, Pengfei; Zhou, Yao; Yang, Xiaoping; Yan, Junjie; Liu, Jiping
Highlights: Components of mixture layer of DCC was experimentally confirmed. Effect of dissolved non-condensable gas on flow patterns was investigated. Influence of non-condensable gas on volumetric heat transfer coefficient was studied. Abstract: An experimental study was performed to investigate the effect of non-condensable gas dissolved in sub-cooled water on steam-water direct contact condensation (DCC). Non-condensable gas dissolved in the sub-cooled water was removed mostly by a degassing membrane device, and the mass fraction of dissolved oxygen was reduced from 7.6 mg/L to 4.6 mg/L and 1.1 mg/L respectively by degassing. Before and after degassing, the flow patterns, thickness of the mixture layer, temperature and pressure distributions, as well as average volumetric heat transfer coefficient were discussed respectively. The visualization results proved that the mixture layer between the water region and steam region mainly consisted of steam, hot water and a small amount of non-condensable gas dissolved out from water at saturated state. Furthermore, the formation mechanism of the mixture layer was qualitatively discussed. Besides, the temperature and pressure distributions on upper and bottom wall were hardly affected by the non-condensable gas dissolved in sub-cooled water. Moreover, the average volumetric heat transfer coefficient was investigated before and after degassing, and it was concluded that the dissolved non-condensable gas had a slight effect on the heat and mass transfer characteristic of DCC process.